An overview on COVID-19 and its impact on migration in Malaysia / Borhan Abdullah ... [et al.] - Abdullah, Borhan; Sareya, Rosli; Andi Kele, Andi Tamsang; Boroh, Rostika P.; Naim, Shafinaz (Faculty of Business and Management, 2021)
The COVID-19 pandemic has affected countries all over the world. Many countries have imposed restrictive measures, such as lockdowns, shelter-in-place, and stay-at-home orders, as an attempt to control the pandemic at a local level. However, these measures also hit the economy hard. This paper predicts the impact of COVID-19 on migration in Malaysia based on the experience during the Asian Financial Crisis. Migrant workers contribute a large portion of the labour market in Malaysia. Thousands of migrant workers are affected due to the COVID-19 pandemic. Besides, the implementation and reimposition of multiple phases of Movement Control Order (MCO) which worsened the economy. Therefore, there is a need to review the possible effect of COVID-19 on migration as it would greatly affect the labour market and the economy as a whole.